1993
DOI: 10.1093/oxfordjournals.aje.a116612
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Exposure to Environmental Tobacco Smoke in Studies of Acute Health Eftects

Abstract: The relations among three methods of measuring exposure to environmental tobacco smoke, questionnaires, urinary cotinine, and a passive monitor for ambient nicotine, were investigated in a study of 48 children in Minnesota in 1989. Subjects were all under 2 years of age and did not attend day care. Passive nicotine monitors were placed in the activity room and the child's bedroom for 1 week, urine samples were collected at the beginning and end of the week for cotinine analysis, and a detailed questionnaire co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 13 publications
4
51
2
2
Order By: Relevance
“…Nicotine concentrations were calculated by dividing the number of micrograms of nicotine collected by the volume of air sampled (the effective sampling rate was 24 ml/min). The samplers have been found to be valid and reliable, and have been used in a variety of field settings (Coghlin et al, 1989;Mumford et al, 1989;Vaughan and Hammond, 1990;Hammond et al, 1993Hammond et al, , 1995Marbury et al, 1993;Emmons et al, 1994).…”
Section: Measurement Of Shsmentioning
confidence: 99%
“…Nicotine concentrations were calculated by dividing the number of micrograms of nicotine collected by the volume of air sampled (the effective sampling rate was 24 ml/min). The samplers have been found to be valid and reliable, and have been used in a variety of field settings (Coghlin et al, 1989;Mumford et al, 1989;Vaughan and Hammond, 1990;Hammond et al, 1993Hammond et al, , 1995Marbury et al, 1993;Emmons et al, 1994).…”
Section: Measurement Of Shsmentioning
confidence: 99%
“…American Chemical Society, 1985). Respirable particulate concentration µg·m -3 Cumulative frequency % and RSP concentrations vary with the ETS source strength, and measurements in field studies have shown that their residential concentrations correlate highly with the reported amount of smoking [29][30][31][32]. For example, LEADERER and HAMMOND [30] reported a field study of 96 residences in Onondaga and Suffolk Counties in New York State, USA, where indoor air vapour-phase nicotine and RSP were monitored over a period of 1 week.…”
Section: Selected Studies Of Indoor Air Nicotine and Rspmentioning
confidence: 99%
“…Questionnaire-derived measures of the level of ETS exposure have been only moderately correlated with body fluid cotinine concentrations among adults, but among children the correlations have been somewhat better [3,7,24,31,36,37,66]. On the other hand, although cotinine levels show considerable individual variability within exposure categories, several studies have demonstrated that average cotinine levels increase with the degree of reported ETS exposure [6].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…We also note that we do not assess conditions in higher income households and therefore Internal validity may be compromised because we report on exposures assessed by caregiver self-report and staff field observation without physical or biological measurements such as antigen load in dust, ambient tobacco levels, urinary/ salivary cotinine levels, or levels of volatile organic compounds. 67 We are collecting quantitative dust samples and will report in future publications on dust loading of bedroom carpets (~tg dust/m 2 carpet), allergen concentrations (mite, roach, cat, and dog) in dust (~tg allergen/g dust), and fungal spore concentrations and type.…”
Section: Mitation5mentioning
confidence: 99%